Soil Bacteria Community Composition Indicating Soil Quality in Different Tillage Practices - Khafida, Wilda; Ratnaningsih, Hanim Rahayuani (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2024)
Organic tillage practice of current study used fully cattle manure, while semi-organic tillage used cattle manure and 10% of synthetic fertilizers as transition to reduce chemical inputs in order to improve sustainable production and ecosystem health. Despite the important role of soil microbes in soil of agriculture, we still have limited understanding of the complex response of microbial composition to organic and semi-organic tillage practices. The aim of this work was to evaluate the impact of use of organic and semi-organic tillage practices on bacteria abundance, richness and functional diversity of microbial communities. Analysis of soil bacteria using nutrient agar by serial dilutions of soil suspension was performed to quantify bacteria abundance. They were further identified and categorized into IAA-producing bacteria and non IAA-producing bacteria groups in Tryptic Soy Agar (TSA). Bacteria abundance was significantly higher in semi-organic tillage than organic tillage. Even though bacteria richness did not show statistically significant, beneficial effect of organic tillage was reflected in higher bacteria richness in term of isolates. The assessment of their functional diversity on producing IAA hormone demonstrated higher IAA-producing bacteria than non IAA-producing bacteria in both tillage practices, indicating the availability of rich substrate through introduction of cattle manure improve soil quality and beneficial for soil bacteria. We observed that among all physicochemical properties, C-organic indicated highly significant, higher in organic tillage than semi-organic tillage. It has been proposed that the availability of organic carbon may favour bacteria as resource of energy.   Keywords: Bacteria community composition; IAA-producing bacteria; Organic tillage; Semi-organic tillage